Implementation of Learning Through Interactive Videos for Early Childhood Education Students Based on Local Wisdom - Putra, Dhiya Restu; Panglipur, Diana Wahyu; Suciati, Romadona Desy; Ramadhani, Desi Dwi; Mahardhani, Ardhana Januar (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Early childhood education (ECE) demands imaginative and inventive approaches to guarantee that children are actively involved and undergo significant learning in line with their developmental phases. The swift advancement of technology has made interactive video a valuable tool for enhancing ECE learning, especially when integrated with local cultural material. This research examines the use of the interactive video Wajanus (Warung Jajanan Nusantara) in Class B of Mutiara Hati Kindergarten Ponorogo, aimed at familiarizing children with Indonesian traditional snacks while also enhancing their cognitive, social, linguistic, and cultural values. A qualitative descriptive method was utilized, involving participatory observation, semi-structured interviews with parents and teachers, along with documentation via photos, videos, and field notes. Data analysis adhered to the model proposed by Miles and Huberman, encompassing data reduction, data presentation, and thematic conclusion formulation. The results indicate that utilizing Wajanus improved children's involvement in cognitive, emotional, and motor skills while promoting greater learning motivation. Children recognized numbers, shapes, and new vocabulary more efficiently, and they exhibited a positive attitude toward the local cultural heritage presented in the video. However, challenges were noted, including differing degrees of child involvement, the demand for extensive teacher assistance, and inadequate educational resources. In summary, interactive videos grounded in local culture like Wajanus are successful in enhancing early childhood education quality while also reinforcing children’s character education and cultural identity, and they possess significant potential for duplication in other ECE institutions throughout Indonesia